2010
DOI: 10.1021/jf9033317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Illicit Dexamethasone upon Hepatic Drug Metabolizing Enzymes and Related Transcription Factors mRNAs and Their Potential Use As Biomarkers in Cattle

Abstract: In cattle fattening, the illicit use of growth promoters (GPs) represents a major problem. The synthetic corticosteroid dexamethasone (DEX) is the GP mostly used, alone or in combination with other steroids or beta-agonists. Recently, GPs were shown to disrupt some cattle cytochromes P450 (CYPs) at the post-transcriptional level; therefore, the effects of two illicit protocols containing DEX (alone or together with 17beta-estradiol, 17betaE) upon main cattle liver drug metabolizing enzymes (DMEs) mRNAs and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 52 publications
5
35
1
1
Order By: Relevance
“…In cattle, the order of magnitude of PB induction was two-to four-times the control value and comparable to the more general CYP3A pattern of up-regulation (Zancanella et al, 2012). Present and previously published data (Greger et al, 2006;Cantiello et al, 2009;Giantin et al, 2010;Zancanella et al, 2012) suggest that differences in CYP3A regulation, expression and function may perhaps exist between cattle and humans. Such a hypothesis is fascinating and worthy of further molecular studies.…”
Section: Discussionsupporting
confidence: 81%
“…In cattle, the order of magnitude of PB induction was two-to four-times the control value and comparable to the more general CYP3A pattern of up-regulation (Zancanella et al, 2012). Present and previously published data (Greger et al, 2006;Cantiello et al, 2009;Giantin et al, 2010;Zancanella et al, 2012) suggest that differences in CYP3A regulation, expression and function may perhaps exist between cattle and humans. Such a hypothesis is fascinating and worthy of further molecular studies.…”
Section: Discussionsupporting
confidence: 81%
“…Initially, quantitative real-time PCR was used to analyze the expression of candidate diagnostic genes. This approach has already been successfully applied in several studies on experimentally treated animals [7-12]. However, good candidate genes are often difficult to identify and the use of single or few gene markers provides a limited and biased view of the biological response to xenobiotics.…”
Section: Introductionmentioning
confidence: 99%
“…A number of novel gene expression profiles have been examined in different bovine tissues, and some of these findings could be applicable in the field as routine screening methods (Toffolatti et al 2006;Reiter et al 2007;Carraro et al 2009;Giantin et al 2010;Lopparelli et al 2010). Recently, De Maria et al (2010 investigated PR mRNA expression in bulbourethral glands as a potential biomarker of illicit 17-oestradiol administration in veal calves and found that it may be a promising new approach to improve the current residue control programmes.…”
Section: Introductionmentioning
confidence: 99%